The rivers of our memory (2014)
The work of the artist Rember Yahuarcani is a visual itinerary through the myths and stories of the beings that populate the physical and spiritual world of Amazonia. The myths are the rivers where the memory of the ancestors navigates and it is there, where Rember has sought the words and images that have guided his creative work. He learned by the side of his father, Santiago Yahuarcani, while at the same time he heard the stories narrated by his grandmother Martha López. Since 2003, he began to exhibit his pictorial work in galleries, but still stereotyped as “indigenous art”. Since 2007, Yahuarcani has strived to “open up spaces” to present his work, no longer with the label “indigenous painting”, but as pieces of contemporary art, truly rooted in indigenous history and tradition, but with an evolution, style and identity of their own.